Decreased quadriceps force steadiness following anterior cruciate ligament reconstruction is associated with altered running kinematics. (February 2020) - Spencer, Alex; Davis, Kylie; Jacobs, Cale; Johnson, Darren; Ireland, Mary Lloyd; Noehren, Brian
Abstract: Background: Anterior cruciate ligament reconstruction is associated with quadriceps dysfunction and altered knee mechanics, but the relationship between these outcomes is not clear. Inclusion of metrics such as the stability of torque output could provide additional insights into the relationship between quadriceps dysfunction and knee mechanics. The purposes of this study were to: (1) measure the difference in quadriceps force steadiness between anterior cruciate ligament reconstructed and contralateral limbs; and (2) assess the relationship of quadriceps force steadiness and peak torque with knee flexion excursion during running. Methods: Twenty-eight participants (14 female, age 20 (5) years) underwent quadriceps strength testing and gait analysis. Force steadiness was measured with the standard deviation and coefficient of variation of the participants' detrended torque. Knee flexion excursion was calculated during the stance phase of running trials. Differences between limbs for force steadiness and peak torque were assessed with paired sample t -tests, and a Pearson's product-moment correlation coefficient determined the relationship between pairs of variables. Findings: Anterior cruciate ligament reconstructed limbs presented with a significant deficit in relative force steadiness compared to the contralateral limb (4.03 (1.04) % and 3.58 (1.41) % ( P  < .05), respectively). In addition, the relationship of quadriceps strength and force steadiness with knee flexion excursion was altered in anterior cruciate ligament reconstructed limbs due to the inability of the quadriceps to sustain a controlled force output. Interpretation: These results suggest that considering both the magnitude and quality of force production can provide important insight into comprehensive quadriceps function. Highlights: Changes in knee mechanics are not fully explained by quadriceps weakness. Anterior cruciate reconstructed limbs display hindered quadriceps force steadiness. Quadriceps force steadiness is associated with altered running kinematics. Quantifying both strength and steadiness helps further elucidate muscle dysfunction.